Covid and the politics of nature. (1st June 2021) - Benton, Ted
Abstract : It is argued that the decades before 2020 saw a steady rise in public concern about and political recognition of symptoms of a crisis in human social and economic relations to (the rest of) nature. For many, the Covid-19 pandemic has become linked to that, as well as providing, despite the grief and suffering, moments when a different relationship to nature could be experienced. The possibility of a transformative politics towards a just reconciliation between social life and nature may be more visible, but will be ruthlessly resisted by those in power.